2019
DOI: 10.1002/fsn3.1241
|View full text |Cite
|
Sign up to set email alerts
|

The hepatoprotective activities of Kalimeris indica ethanol extract against liver injury in vivo

Abstract: Kalimeris indica (L.) Sch. Bip. is a traditional Chinese medicine (TCM) and a portion of food used for cooking in China. It has been demonstrated that an ethanol extract of K. indica has an anti‐inflammatory effect by inhibition of nitric oxide (NO) production on murine macrophage RAW264.7 cells after lipopolysaccharide (LPS) induction. In this study, the hepatoprotective effects of the total phenolics of K. indica (TPK), the total triterpenes of K. indica (TTK), and the total flavones of K. indica (TFK) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Plant extracts contain phytochemicals which are active in preventing various diseases and may be beneficial to health with moderate consumption. Many studies have explored the potential of plant extracts against liver injuries (Park et al., 2020 ; Wang et al., 2019 ; Zhu et al., 2019 ). The pathology of I/R‐induced hepatic injury reveals that oxidative stress plays a crucial role in the scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts contain phytochemicals which are active in preventing various diseases and may be beneficial to health with moderate consumption. Many studies have explored the potential of plant extracts against liver injuries (Park et al., 2020 ; Wang et al., 2019 ; Zhu et al., 2019 ). The pathology of I/R‐induced hepatic injury reveals that oxidative stress plays a crucial role in the scenario.…”
Section: Discussionmentioning
confidence: 99%
“…The pre exposure of liver to the chemicals results in liver injury. CCl4, a potent hepatotoxic agent, is mostly used to study hepatoprotective activity of medicinal plants (Wang et al, 2019).The protective effect of fig fruit on liver enzymes and protein were shown in Figure 1. Induction of CCl4 significantly increased (P < 0.05) the level of liver markers such as alanine transaminase, aspartate aminotransferase, alkaline phosphatase and bilirubin as compared to the normal group.…”
Section: Hepatoprotective Studymentioning
confidence: 99%
“…Previously published research report by Wang et al. ( 2019 ) has reported on about Kalimeris indica ethanolic extract in vivo hepatoprotective effects. The authors have concluded that the extract led to improvement in liver injury in mice and decreasing tendencies in hepatic malondialdehyde (MDA) content and total nitric oxide synthase (tNOS) levels.…”
Section: Introductionmentioning
confidence: 99%